Carbon nitride derived nitrogen-doped carbon nanosheets for high-rate lithium-ion storage. (21st September 2021) - Zhang, Wenli; Yin, Jian; Chen, Cailing; Qiu, Xueqing
Graphical abstract: Highlights: Graphitic carbon nitride is zinc-thermally transformed into nitrogen doped carbon. The underlying mechanism was elucidated by TGA-MS spectra. The obtained nitrogen doped carbon shows superior Li-storage performance. This paper proposes a general strategy for the preparation of nitrogen-doped carbon. Abstract: Carbonaceous materials are practical anodes for lithium-ion batteries. Commercial graphite anode has a limited theoretical capacity of 372 mAh g −1 . Amorphous carbon anode could break the capacity limitation of the graphite anode, while nitrogen doping plays a critical role in effectively enhancing the reversible capacities and rate capability of carbonaceous anodes. Herein, we propose a new strategy for synthesizing nitrogen-doped carbon materials from graphitic carbon nitride. Zinc-assisted thermal treatment of graphitic carbon nitride enables the carbonization of graphitic carbon nitride and successful preparation of highly nitrogen-doped carbon. The obtained nitrogen-doped carbon material is doped with a high-level nitrogen of 21.6 at. % which enables high reversible capacity and rate capability. This work puts forward a new synthesis protocol of nitrogen-doped carbon materials for promising anodes of lithium-ion batteries.